Digital Entrepreneurship: How F-commerce is Revolutionizing Women's Economic Opportunities in Bangladesh - Talukder, Md. Uzzal (Khulna University Studies, 2026)
This study examines the transformative impact of F-commerce on empowering women entrepreneurs in Bangladesh, focusing on the economic opportunities it offers. As technology becomes increasingly integrated into daily life, platforms like Facebook are reshaping traditional business models, particularly for women. The research uses a qualitative approach, conducting in-depth interviews with 20 women entrepreneurs from all eight divisions of Bangladesh and the data were analyzed using thematic analysis. The findings reveal key benefits, including financial independence, social empowerment, and flexibility, which allow women to balance professional and personal responsibilities. Despite these advantages, challenges such as poor internet connectivity, delivery issues, societal resistance, and cybersecurity threats persist. The study also highlights how the COVID-19 pandemic significantly accelerated women’s participation in F-commerce, with many achieving substantial income and social recognition. The interviews underscore the importance of strong support systems to sustain success in the sector. Based on these insights, the study calls for targeted interventions by government agencies, policymakers, and relevant stakeholders, including digital literacy programs, improved logistics infrastructure, and practical training, to enhance women’s involvement in F-commerce. The findings highlight the potential of F-commerce to address unemployment and empower women, urging policymakers and stakeholders to support this emerging sector through strategic initiatives and continued development. This study contributes to the growing body of literature on digital entrepreneurship and women’s economic empowerment in developing countries, particularly in the context of Bangladesh.